Three prolonged outbreaks of metallo-β-lactamase-producing Pseudomonas aeruginosa in an Upper Austrian hospital, 2017–2023 - Adriana Cabal; Anna Hörtenhuber; Yarub Salaheddin; Anna Stöger; Burkhard Springer; Stefan Bletz; Alexander Mellmann; Patrick Hyden; Rainer Hartl; Johannes Weinberger; Rick Conzemius; Markus Hell; et al. (Microbiology Spectrum, 2024)
ABSTRACT In spring 2022, an increase in metallo-β-lactamase-producing Pseudomonas aeruginosa (MBL-Pa) infections was detected in a hospital in Upper Austria. To identify the source of infection and to stop further transmissions, an epidemiological outbreak investigation including whole-genome sequencing (WGS)-based typing was conducted. The final case definition included cases admitted to the hospital between 2020 and 2023 with an MBL-Pa in one of the three genomic clusters identified. In addition, the investigation was extended to include historical cases from 2017. Core genome multilocus sequence typing was performed to assess the genetic relatedness between the isolates. Fifty-four clinical P. aeruginosa isolates and eight P. aeruginosa isolates from the hospital environment were obtained. All but nine isolates grouped into one of three genomic clusters (ST235/blaVIM-1, ST111/blaVIM-2, or ST621/blaIMP-13), which were considered to be distinct, prolonged outbreaks involving 47 out of 52 cases. The most likely source of infection for cluster 1 (ST111/blaVIM-2) and cluster 2 (ST235/blaVIM-1) was sinks in the intensive care unit (ICU) washroom. Cluster 3 clone (ST621/blaIMP-13) could have originated in the urology ward in 2020 and then spread to the ICU years later. However, the nosocomial origin of this clone could not be proven. In March 2023, following the implementation of control measures (gowning, patient isolation, screening, and daily disinfection), no further MLB-Pa was detected, and the outbreaks were considered to be over. As ICUs play an important role in the transmission of P. aeruginosa, emphasis should be placed on genomic surveillance, infection prevention, and control in such wards.IMPORTANCEThe significance of our work lies in the successful resolution of three prolonged outbreaks of MBL-Pa infections in a hospital in Upper Austria. Through a comprehensive epidemiological investigation coupled with WGS-based typing of P. aeruginosa isolates, the study identified three distinct genomic clusters responsible for prolonged outbreaks involving 47 cases. The investigation pinpointed sinks in the ICU washroom as the likely source of infection for two of the clusters. The study demonstrates the effectiveness of control measures such as hand hygiene, gowning, patient isolation, screening, and disinfection in stopping further transmission and bringing the outbreaks to a close. This underscores the critical role of genomic surveillance and control measures, particularly in high-risk settings like ICUs, in reducing nosocomial transmission of MBL-Pa infections.